Legal Accountability of Local Government in Handling Child Violence Cases - Jhohannes H. Situmorang; Andryan (International Journal of Society and Law, 2026)
Child violence is an urgent legal issue in Indonesia, including in North Labuhanbatu Regency, which still faces institutional capacity limitations in handling such cases. This study aims to analyze the authority of local governments in handling child violence cases based on applicable legislation, as well as to examine the forms of legal accountability applicable to local governments in cases of negligence or inaction. The research employs a normative juridical method with statutory, case-based, and comparative approaches. Data were obtained from literature studies, legal documents, and interviews with stakeholders in North Labuhanbatu Regency. The findings indicate that local governments possess authority derived from Law Number 23 of 2014 on Regional Government, Law Number 35 of 2014 on Child Protection, and Presidential Regulation Number 101 of 2022 concerning the National Strategy for the Elimination of Violence against Children.However, implementation remains hampered by overlapping regulations, budgetary constraints, and weak inter-agency coordination. Legal accountability of local governments can be constructed through administrative law and civil law mechanisms on the basis of onrechtmatige overheidsdaad. This study concludes that strengthening regional regulations, enhancing institutional capacity, and integrating unified reporting systems are strategic measures for advancing child protection at the local level.